2011
DOI: 10.1258/ijsa.2011.010492
|View full text |Cite
|
Sign up to set email alerts
|

Reticence to prescribe: utilization of expedited partner therapy among obstetrics providers in Arizona

Abstract: Expedited partner therapy (EPT) is the practice of providing an extra dose or prescription of antibiotic to patients diagnosed with chlamydia or gonorrhoea to deliver to their sexual partner(s). Obstetrical providers who delivered more than 20 infants in Maricopa County, Arizona, USA, during the year 2008 were surveyed by telephone regarding their use of EPT. A total of 142 eligible respondents completed the survey, representing 34% (142/421) of the delivering providers, 67 (47%) of whom reported the use of EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The provision of EPT in women's health-care settings is an accepted option for partner treatment. 12,16,18 These findings positively reflect the patient follow-up practices of the primary and women's clinics at this facility and highlight opportunities to expand the delivery of EPT for patients diagnosed in urgent and emergent care settings.…”
Section: Discussionmentioning
confidence: 60%
“…The provision of EPT in women's health-care settings is an accepted option for partner treatment. 12,16,18 These findings positively reflect the patient follow-up practices of the primary and women's clinics at this facility and highlight opportunities to expand the delivery of EPT for patients diagnosed in urgent and emergent care settings.…”
Section: Discussionmentioning
confidence: 60%
“…[15] Lastly, provider knowledge of EPT is associated with higher rates of practice, yet practice is inhibited by concern for legal liability. [16] Concern for liability exists because EPT involves prescribing and dispensing medications to individuals who have not been physically examined by a healthcare provider. Potential legal actions include medical malpractice lawsuits from individuals or censure from state professional licensure boards.…”
mentioning
confidence: 99%
“…Some patients are averse, however, reinforcing the need for providers to discuss options with patients. One survey of obstetricians and gynecologists in Arizona found that almost one-third of respondents were reluctant to prescribe EPT because of allergy-related concerns, whereas another 11% did not prescribe EPT due to liability concerns [24]. Reasons for ambivalence vary, but often include worries about allergic reactions, liability, and incomplete care when partners do not seek evaluation.…”
Section: Uptakementioning
confidence: 99%
“…Of 466 patients treated for chlamydia in 2004-2005, 323 (69%) were provided with EPT after a discussion with their provider. The Arizona survey cited above also found that providers who were informed of guidelines permitting EPT were more likely to prescribe EPT, 69 vs. 44% [24]. Baltimore STD clinics [17] have reported substantial proportions of individuals receiving EPT (68%), as has an STD clinic in San Francisco (43%, with almost identical rates of uptake among heterosexual patients and MSM) [18].…”
Section: Uptake Evaluationmentioning
confidence: 99%